The Role Of Parents In Islamic Perspective Sex Education For Adolescents - Amrulloh Karim; Muhammad Najib (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2024)
Sex education is not about supporting children to have sexual relations but explaining the natural function of sex as part of themselves and the consequences if misused. Parents are the main actors in children's education. Parents serve as the primary educational facilitators for children, as they are the most suitable individuals to impart sex education during early childhood and adolescence. Parents no longer need to doubt the importance of sex education from an early age. Eliminate the feeling of awkwardness that exists and start building sensitivity to the need for sex education in children. The aim of this research is to analyze the role of parents in providing sex education for teenagers and to analyze the inhibiting factors in providing sex education for teenagers. This research type utilizes naturalistic phenomenology and employs a qualitative descriptive approach. Data collection methods in this research used interviews, observation, and documentation. Next, to check the validity of the data, the author uses triangulation techniques. Then, to analyze the data, the author divides it into three components: data reduction, data display (data presentation), and drawing conclusions (data verification). The research findings reveal that parents at MTs Tarbiyatul Wathon Campurejo Panceng Gresik provide sex education to teenagers; however, despite this, some children continue to engage in deviant behavior. Some parents still maintain a taboo against imparting sex education to teenagers. Furthermore, the obstacles to implementing sex education for teenagers include parents' lack of knowledge about sex education, their inability to communicate it effectively, their lack of openness with children, and the limited intensity of meetings between children and parents. Parents coordinate well between religious leaders, community leaders, and village health workers, such as village midwives or village orderlies, regarding sex education for teenagers through socialization. Try to prevent it by giving warnings and punishments if children do deviant things, accompanied by an understanding so they don't do it again.